Jeremy Adelman, Worldly Philosopher. The Odyssey of Albert O. Hirschman - Jelin, Elizabeth (Prismas - Revista de historia intelectual, 2014)
Jeremy Adelman, Worldly Philosopher. The Odyssey of Albert O. Hirschman, Princeton, Princeton University Press, 2013, 740 páginas